Autor y lector en la traducción catalana del Decamerón de Boccaccio: análisis de una asimilación. - RECIO, ROXANA (Scripta, 2013)
This paper analyzes the 1429 Catalan translation of Boccaccio's Decameron focusing on its main narrative characteristics, especially the relationship between the author and his readers. While not neglecting basic features of the translation in the period, the main emphasis is placed in the significance of this text, sometimes considered a simple adaptation, as a Humanist work, a document of the assimilation of Italian Humanism in the Crown of Aragón. This Catalan text constitutes an example of how Boccaccio's narrative ideas were understood at the time, for many of the so called defects in this translation are the result of narrative strategies addressed to a specific audience and culture. We are in front of translators interested in literary creation and in the quest for beauty in their work, which reflects the close relationship between Boccaccio's new style and the Catalan author's/authors' approach. It should not be viewed as a mere translation.